Pharmacological Hypotension as a Cause of Delirious Mania in a Patient with Bipolar Disorder. (19th December 2017) - Carbone, Manuel Glauco; Miniati, Mario; Simoncini, Marly; Tripodi, Beniamino; Tagliarini, Claudia; Carmassi, Claudia; Dell'Osso, Liliana
Abstract : Delirious mania is a severe but often underrecognized syndrome characterized by rapid onset of delirium, mania, and psychosis, not associated with a prior toxicity, physical illness, or mental disorder. We discuss the case of a delirious mania potentially triggered and maintained by a systemic hypotension induced by antihypertensive drugs. Symptoms recovered completely after the discontinuation of antihypertensive medications and the normalization of blood pressure levels.